BUDAYA ORGANISASI, KOMPENSASI, KEPUASAN KERJA, KOMITMEN ORGANISASI DAN KINERJA Di KPP PRATAMA SE BADUNG - I Nyoman Alit Arsa Aryana (Universitas Pendidikan Nasional, 2014)
Directorate General of Taxes (DGT) as one of public institutions in Indonesia whosefunctions and duties are to implement government’s taxation plans and policies as well as tocollect more than 70% of its national annual budget from tax revenues, is expected to show anexcellent organization performance. However, for the last five years it hasn’t shown theperformance as it is expected. This becomes a big challenge for DGT to prove to itsstakeholders that the bureaucracy reform which has been run in DGT is on the right track.Some of the internal problems are believed as the culprit of such government institution’s lowperformance, including DGT’s performance. Studies have shown that variables such asorganization’s culture, compensation, job’s satisfaction, and organization commitment have astrong correlation with the performance of the organization. To that regards, the aims of thisstudy is to determine whether there is a positive and significant effect of organization’s culture,compensation, job’s satisfaction, and organization commitment in improving the performanceof the organization, and also to examine which one of those factors has the strongest effect.For that purpose, this study takes a population and collect data from 160 employees of TaxOffice in Badung Regency Area using the Structural Equation Modelling (SEM) analysis. Theresults show that the organization culture has a positive and significant effect on employee’sjob's satisfaction and performances, and so does the compensation. While the job’s satisfactionpositively and significantly affects the organization commitment, and the organizationcommitment affects the job's satisfaction positively and significantly.Keyword: organization’s culture, compensation, job’s satisfaction, organizationcommitment and performance of the organization.